Inovasi Pelayanan Pembayaran Retribusi (Myretribusi) dalam Peningkatan Pelayanan Badan Pelayanan Pajak Daerah (BPPD) Kabupaten Sidoarjo - Bagus Mohammad; Eva Hany Fanida; Meirinawati M; Trenda Aktiva Oktariyanda (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
MyRetribusi is an innovation in the form of an e-government-based application that supports transparency, accountability, and efficiency in the regional revenue collection process in the retribution sector. This study aims to describe the innovation of retribution payment services through the MyRetribusi application in improving the services of the Regional Tax Service Agency (BPPD) of Sidoarjo Regency. This research uses a descriptive qualitative method with data collection techniques through observation, interviews, and documentation. The analysis focuses on the public sector innovation success theory by Bugge et al. (2018), which includes innovation governance, sources of innovation ideas, innovation culture, capabilities and tools, objectives, outcomes, drivers, obstacles, and data collection for single innovation. The results show that the MyRetribusi innovation was developed in response to retribution payment problems that were still carried out manually, were inefficient, and were prone to reporting irregularities. This innovation is supported by local regulations, cross-sector collaboration, and socialization through social media and direct outreach. In addition to facilitating digital retribution payments, MyRetribusi also improves transparency, data accuracy, and service efficiency. However, its implementation still faces obstacles such as user adaptation, inter-agency coordination, and strengthening human resource capacity. Overall, MyRetribusi shows that the digitalization of retribution services can improve the quality of public services in Sidoarjo Regency.